So, you want to host an inclusive and accessible conference? - Ana Sofia Barrows; Mahadeo A. Sukhai; Imogen R. Coe (Canadian Science Publishing, 2021)
In 2017 at the Gender Summit in Montreal, Québec, Chief Science Advisor of Canada, Dr. Mona Nemer, stated the importance of promoting diversity in Science, Technology, Engineering, and Mathematics (STEM). She emphasized that "increasing the number and impact of women and other members of underrepresented groups in STEM requires the concerted efforts of our entire society-including governments, scientific organizations, research granting agencies, and educational institutions" (Nemer 2017). The following year, the Tri-Council (Natural Sciences and Engineering Research Council, Canadian Institutes of Health Research, and Social Sciences and Humanities Research Council) created an Equity, Diversity and Inclusion (EDI) Action Plan, with one of its key objectives being the development of initiatives to foster inclusive participation in the research system (Canada Research Coordinating Committee 2018). The aim of these initiatives is to increase participation of the four designated groups-women, persons with disabilities, members of visible minorities or racialized groups, and Indigenous Peoples-and members of the LGBTQ2+ communities as mandated by the Tri-Council (Government of Canada 2019).